2018
DOI: 10.20471/acc.2018.57.03.14
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Appendectomy does not Increase the Rate of Negative Appendectomy along with a Lower Rate of Perforated Appendicitis – Results in 1899 Patients at Zagreb UHC

Abstract: SUMMARY – Laparoscopic appendectomy is the method of choice of many professional societies owing to its many advantages. The question arises whether surgeons urge more easily to laparoscopic exploration due to its less invasiveness, faster recovery and adequate exploration of the entire abdominal cavity than to observation in unequivocal cases. This retrospective analysis (2009-2016) included 1899 patients undergoing laparoscopic (lap) or gridiron intra-abdominal approach treated at Zagreb University Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The criteria for calculating the incidence of negative appendectomies are described in detail in this study. Our results of the overall incidence are comparable and similar to the results of studies published so far on the incidence of negative appendectomies in children and adults [28,29,31]. Some authors doubted whether the laparoscopic approach increases the number of negative appendectomies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The criteria for calculating the incidence of negative appendectomies are described in detail in this study. Our results of the overall incidence are comparable and similar to the results of studies published so far on the incidence of negative appendectomies in children and adults [28,29,31]. Some authors doubted whether the laparoscopic approach increases the number of negative appendectomies.…”
Section: Discussionsupporting
confidence: 90%
“…Some authors doubted whether the laparoscopic approach increases the number of negative appendectomies. A recent study clearly showed that laparoscopic appendectomy should be offered as the method of choice in any patient population with suspicion of acute appendicitis and that the laparoscopic approach does not increase the number of negative appendectomies [31].…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in medicine, acute appendicitis is still a diagnostic problem and a challenge for even experienced emergency physicians and pediatric surgeons. The latter is demonstrated by the high negative appendectomy rates, ranging between 10% and 20%, documented in the literature [ 6 , 7 , 8 , 9 ]. The aforementioned negative appendectomy rate can be significantly lowered to 2.7% with the routine use of imaging [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…An overview of malignant findings can be seen in Table 2. Only 5 studies [18, 31, 36, 38, 42] did not mention malignancy, while all other studies had at least two categories such as “malignancy” and “other findings.” Meta-analysis showed that patients operated for suspected acute appendicitis had an estimated rate of malignancy of 1% (95% CI 0.8–1.3) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%